2021
DOI: 10.3389/fimmu.2021.688254
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Regulation of CNS Barriers After Traumatic Brain Injury: A Tale Directed by Interleukin-1

Abstract: Several barriers separate the central nervous system (CNS) from the rest of the body. These barriers are essential for regulating the movement of fluid, ions, molecules, and immune cells into and out of the brain parenchyma. Each CNS barrier is unique and highly dynamic. Endothelial cells, epithelial cells, pericytes, astrocytes, and other cellular constituents each have intricate functions that are essential to sustain the brain’s health. Along with damaging neurons, a traumatic brain injury (TBI) also direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 190 publications
1
17
2
Order By: Relevance
“…Based on our results, microglial activation clearly occurred in both the sTBI and rmTBI models. This suggests that the assumption from previous research about only 40% of TBI patients having a negative retinal impact appears to be highly underestimated [12]. Surprisingly, although we observed a high level of activation at sTBI, the data measured in rmTBI was not far behind those measured in sTBI, which may be alarming in cases where someone (e.g., sports such as football, boxing) is continuously exposed to minor cranial injuries [29].…”
Section: Microglial Activation Due To Traumatic Brain Injurycontrasting
confidence: 75%
See 1 more Smart Citation
“…Based on our results, microglial activation clearly occurred in both the sTBI and rmTBI models. This suggests that the assumption from previous research about only 40% of TBI patients having a negative retinal impact appears to be highly underestimated [12]. Surprisingly, although we observed a high level of activation at sTBI, the data measured in rmTBI was not far behind those measured in sTBI, which may be alarming in cases where someone (e.g., sports such as football, boxing) is continuously exposed to minor cranial injuries [29].…”
Section: Microglial Activation Due To Traumatic Brain Injurycontrasting
confidence: 75%
“…1; [11]). TBI also includes retinal injury, which, according to current data, occurs in 20-40% of affected millions in TBI [12]. Mapping these lesions and also milder effects on the retina may help to understand the pathophysiology of TBI and may be an indicative factor in screening for severe cases.…”
Section: Of 16mentioning
confidence: 99%
“…Circulating neutrophils are the main infiltrating peripheral immune cells within one hour and peaking by 24 h post-injury (Gelderblom et al 2009 ). Previous studies demonstrated that neutrophil depletion reduced BBB leakiness after brain injury (Bodnar et al 2021 ; Wei et al 2021 ). Conversely, the increased permeability of BBB facilitates neutrophil infiltration into the brain after ischemic stroke (Obermeier et al 2013 ).…”
Section: Discussionmentioning
confidence: 94%
“…Circulating neutrophils are the main infiltrating peripheral immune cells within one hour and peaking by 24 h post-injury (Gelderblom et al 2009). Previous studies demonstrated that neutrophil depletion reduced BBB leakiness after brain injury (Bodnar et al 2021;Wei et al 2021).Conversely, the increased permeability of BBB facilitates neutrophil infiltration into the brain after ischemic stroke (Obermeier et al 2013).In this study, SA treatment significantly decreased the neutrophil/macrophage infiltration into the brain tissue while not altering the peripheral immune cells, suggesting that SA may play an immunomodulatory role though preserving BBB integrity. The cadaverine leakage density and plasma IgG leakage detection further demonstrated the beneficial effect of SA on the BBB.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, pvBAMs may contribute to vascular inflammation, blood–brain barrier (BBB) permeability, nutrient exchange, and metabolism, as well as HPA axis regulation [ 70 , 71 ]. Given that the choroid plexus interfaces between the periphery and CNS, immune cell activation in this compartment may aid in T-cell trafficking and antigen presentation in the meninges [ 67 , 68 , 72 ], along with neutrophil invasion [ 69 , 73 ]. With an opportune location, cpMɸ are crucial in the development of neurological sequalae of multiple sclerosis (MS), experimental autoimmune encephalomyelitis (EAE), and TBI.…”
Section: Distinct Role For Microglia and Other Myeloid Cells In The N...mentioning
confidence: 99%